If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16b + -9b + -1b = 18 Combine like terms: 16b + -9b = 7b 7b + -1b = 18 Combine like terms: 7b + -1b = 6b 6b = 18 Solving 6b = 18 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '6'. b = 3 Simplifying b = 3
| y=-5t^2+20t+60 | | √2/2x-54=1/3 | | ln0.9/ln2= | | 17c+2c+2c-12c=9 | | 2t-2t+4t+t-3t=20 | | 7(2x+7)= | | 3p-2p+p= | | (a-2)/2=-1 | | 4(c-5)=12 | | 21=-3(1-2x)-6(x-5) | | 6r-r=20 | | -4x-5=-4x+13 | | 2(7x+1)= | | 17c-16c=7 | | 1x^3-12x+8=0 | | 2x^2+11x-63= | | 2x+3(2x-1)=25 | | 8.5y=-153 | | 0.88=5c+3c | | 17y=8y+81 | | 3x+-16=180 | | -8(-7p+1)=328 | | 800*5*x=250 | | 6x-9/7=10x | | 14-3w=4w | | 12x^2+15x+3= | | -2y=-4x-20 | | (Y+9)*(y+2)= | | 1.17x=4.68 | | 8=-b/6 | | 6(x+1)=-x+3(2x-2) | | (Y+9)(y+2)= |